1994
DOI: 10.1029/93jb02568
|View full text |Cite
|
Sign up to set email alerts
|

On the temporal evolution of high‐temperature hydrothermal systems at ocean ridge crests

Abstract: The results of heat balance calculations for a single‐pass hydrothermal system overlying an axial magma body, based on a given rate of heat output of 102–103 MW at a time t0, predict that vent temperatures should decay rapidly for t > t0, as the magma freezes and the boundary layer between the hydrothermal system and liquid magma thickens. The model may describe a declining phase of high‐temperature, high‐heat‐output hydrothermal activity. The model shows that for systems with heat output ∼100 MW or greater, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 51 publications
(45 reference statements)
9
78
0
Order By: Relevance
“…Initially, single-phase fluid with the properties of pure water was considered as the convecting fluid for hydrothermal systems at mid-ocean ridges [e.g., Brikowski and Norton, 1989;Lowell and Burnell, 1991;Lowell and Germanovich, 1994;Wilcock, 1998]. Later boiling was considered, but the fluid was still single pure water [Lowell and Xu, 2000;Coumou et al, 2006].…”
Section: Previous Work On Two-phase Flow Simulations On Hydrothermal mentioning
confidence: 99%
“…Initially, single-phase fluid with the properties of pure water was considered as the convecting fluid for hydrothermal systems at mid-ocean ridges [e.g., Brikowski and Norton, 1989;Lowell and Burnell, 1991;Lowell and Germanovich, 1994;Wilcock, 1998]. Later boiling was considered, but the fluid was still single pure water [Lowell and Xu, 2000;Coumou et al, 2006].…”
Section: Previous Work On Two-phase Flow Simulations On Hydrothermal mentioning
confidence: 99%
“…Thus equations (17) and (18) indicate that crustal sealing as a result of precipitation of anhydrite upon mixing between hot sulfate-free hydrothermal fluids and cooler, sulfate-rich seawater can occur on a timescale of years provided the permeability of the pillows (where mixing occurs) and the sheeted dikes are roughly equal and range between 10 À11 and 10 À12 m 2 . These values of ridge axis crustal permeability are of the same order as estimated from measurements in ophiolites [Nehlig and Juteau, 1988;Nehlig, 1994;van Everdingen, 1995] and from hydrothermal modeling of black smoker flow [e.g., Lowell and Germanovich, 1994].…”
Section: Bulk Mixing In High-temperature Discharge Systemsmentioning
confidence: 59%
“…150°C. It is generally thought that flow resistance in the recharge zone is much less than that of the discharge zone [e.g., Lowell and Germanovich, 1994;Pascoe and Cann, 1995]. If we ignore the resistance in the recharge zones and write the term on the right hand side of equation (8) as f(c, x), we find the relation between k m and the permeability in the deep discharge zone k d…”
Section: Bulk Mixing In High-temperature Discharge Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus temporal variability of seafloor hydrothermal discharge occurs on relatively short time scales and careful monitoring of hydrothermal evolution following magmatic events could provide useful constraints on numerical models that address temporal variability. Lowell and Germanovich [1994] provided simple analytical results on the decay of hydrothermal output following magmatic heat input and suggested that thermoelastic stresses could strongly affect the temporal evolution and stability of a black smoker vents on a time scale of years to decades. Germanovich et al [1996] showed that thermoelastic processes in upflow zones following magmafie events could lead to oscillatory hydrothermal output on a timescale of years.…”
Section: Implications For Temporal Variability Of Midocean Ridge Hydrmentioning
confidence: 99%